Identification of mechanical and sound absorption properties of porous concrete containing different amounts of palm oil clinker / Galip, N. S. ... [et al.] - Galip, N. S.; Haron, Z.; Zamri, N. F.; Mohamed, R. N.; Darus, N.; Yahya, K.; Kassim, A. S. F. A.; Redzuan, I. H.; Jahya, Z.; Yahya, M. N.; Din, N. C. (UiTM Press, 2024)
Palm oil clinker (POC) is an industrial waste by-product of the palm oil industry that is usually dumped into landfills. This paper identified the mechanical and sound absorption properties of porous concrete (PC) when different amounts of porous POC aggregates were used. In addition, an ultrasonic pulse velocity (UPV) test was performed to explain the specimen porosity which affected the properties of concrete. POC with a size of 2.36 mm – 6.7 mm was used at 25%, 50%, 75%, and 100% as a substitute for river sand. Compressive strength, density, and UPV decreased as the percentage of POC increased. Replacement of 100% POC reduced the strength by 62%, density by 30%, and UPV by 16% as compared to without POC. A reduction in the UPV value indicated an increase in the porosity of concrete due to the macropores in POC aggregates. The highest improvement of 673% in average sound absorption coefficient for 100% POC as compared to PC which used sand at 250 Hz – 1250 Hz for 75 mm specimen thickness. Compressive strength data showed that specimens with 100% POC exceeded the minimum limit for a PC barrier layer. Therefore, 100% POC with 75 mm thickness had the potential to be applied as a barrier component.